MAVS Ubiquitylation: Function, Mechanism, and Beyond - Hongliang Dong; Jie Shen (Frontiers in Bioscience-Landmark, 2024)
The mitochondrial antiviral-signaling protein (MAVS), a core adaptor protein in the retinoic-acid-inducible gene-I-like receptors (RLRs)-MAVS pathway, has been demonstrated to play an important role in antiviral immune response and tumor immunology. Previous studies revealed that ubiquitylation is a key mechanism in the regulation of the RLRs-MAVS axis and immune response. Multiple E3 ubiquitin ligases and deubiquitinating enzymes control MAVS ubiquitylation and changes in MAVS function. In this review, we summarize the biological function of ubiquitylation in MAVS-related signaling and provide new insight into immunotherapy approaches that target MAVS.